Analisis Pengalaman Pengunjung dan Manajemen Risiko di Kawasanwisata Pondok Halimum - Lutpiah, Dwi; Destriani, Saila; Pauziah, Zahra (PT Alahyan Publisher Sukabumi, 2025)
This study aims to analyze the influence of risk management on visitor experience at the natural tourism destination of Pondok Halimun, Sukabumi. Using a mixed-method approach, quantitative data were collected through questionnaires distributed to 32 visitors, while qualitative data were obtained through semi-structured interviews with site managers. Quantitative analysis included validity testing, reliability testing, simple linear regression, and coefficient of determination, while qualitative data were analyzed using the Miles and Huberman model. The results show that risk management has a significant effect on visitor experience, indicated by a significance value of 0.000 and an R² of 0.615, meaning that 61.5% of visitor experience variation is explained by the quality of risk management. Qualitative findings reveal that risk management practices remain informal, lacking written SOPs, adequate safety facilities, and structured risk communication. These limitations contribute to low perceptions of safety, despite visitors rating the natural scenery highly. The study concludes that strengthening risk management is essential for enhancing the overall visitor experience. Recommendations include developing formal safety SOPs, improving safety facilities, enhancing visual risk communication, providing staff training, and strengthening multi-stakeholder collaboration in destination management.